The Application of Oxytocin Massage to Increase Breast Milk Production in Postpartum Mothers in the Mawar Room of Kardinah Regional General Hospital, Tegal City - Gina Inayati, Putri; Wahyuni Romadhon, Lily; Setyo Dwi Andhini, Citra (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Breastfeeding is very important for a mother for the development and growth of her child. Breastfeeding problems often occur in mothers due to low milk production in the first few days postpartum, which becomes an obstacle in providing exclusive breastfeeding to their babies. This case study aims to determine the application of oxytocin massage in increasing milk production in postpartum mothers. Method: The research design used in this study is descriptive with a case study method. The subject of the case study is Mrs. N, a postpartum mother on her first day in the Mawar Ward of Kardinah General Hospital in Tegal City. Result: The results of the case study conducted over three days showed an increase in breast milk production in Mrs. N, as evidenced by: the client stating that her breast milk flowed smoothly after the oxytocin massage. Conclusion: The application of oxytocin massage as a nursing intervention for Mrs. N, who was experiencing breastfeeding issues, was proven to be effective in increasing breast milk production. This intervention was conducted over three days and showed positive results on the third day, indicating that oxytocin massage could serve as an effective alternative intervention to address insufficient breast milk supply.